2022
DOI: 10.1111/inm.13002
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the experience of seclusion in a forensic setting? An integrative literature review

Abstract: Seclusion is used in forensic and general mental health settings to protect a person or others from harm. However, seclusion can result in trauma-related harm and re-traumatization with little known about the experience of seclusion for consumers in forensic mental health settings from their perspectives. This article explores consumer experiences of seclusion in forensic mental health settings and explores the differences between female and male experiences of seclusion. Five electronic databases were systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Participants in this study reported unmet care needs during PR, such as neglect, lack of care and compassion by healthcare professionals, which is similar to findings in a number of related studies. 8 , 10 In many cases, the main cause of patient dissatisfaction with PR is the lack of contact with the nurse and the feeling of abandonment. 21 The lack of psychiatric nurses and lack of time make it difficult for staff to provide more time with restrained patients, which is the underlying cause of these feelings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in this study reported unmet care needs during PR, such as neglect, lack of care and compassion by healthcare professionals, which is similar to findings in a number of related studies. 8 , 10 In many cases, the main cause of patient dissatisfaction with PR is the lack of contact with the nurse and the feeling of abandonment. 21 The lack of psychiatric nurses and lack of time make it difficult for staff to provide more time with restrained patients, which is the underlying cause of these feelings.…”
Section: Discussionmentioning
confidence: 99%
“… 9 To date, other countries have published a large number of studies on the qualitative experience of restraint in patients with mental disorders, and based on the findings, have developed PR reduction strategies that are suitable for their own national conditions, such as staff training, trauma-informed care, etc., which can reduce the use of PR and minimize trauma. 7 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…The seclusion of patients is often accompanied by negative experiences (Ezeobele et al., 2014). Several other studies have reported patients expressing a feeling of neglect and lack of care while in seclusion, ultimately portraying a lack of therapeutic connection and relation (Askew et al., 2019; Hansen et al., 2022; Holmes et al., 2015; Meehan et al., 2000; Ntsaba & Havenga, 2008). However, strong patient–staff relational contact during seclusion may ameliorate such adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Current research on using seclusion in mental health has demonstrated diverse experiences of seclusion practices for the therapeutic relationship between patients and staff. These experiences may range from patients experiencing support and safety (Ezeobele et al., 2014; Iversen et al., 2011) to experiences of being in a situation of neglect and lack of care (Askew et al., 2019; Hansen et al., 2022; Holmes et al., 2015; Ntsaba & Havenga, 2008) and nurses' feelings of delivering extra care via seclusion (Holmes et al., 2015). Feeling a connection to staff and having relevant access to communication between patients and staff during seclusion has, however, commonly been underlined as a salient condition that may help promote strong patient–staff relationships that ameliorate the adverse effects of seclusion (Berg et al., 2023, Ezeobele et al., 2014, Askew et al., 2019).…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation